A review on fish‐borne zoonotic parasites in Iran. Issue 2 (21st October 2022) - Hajipour, Nasser; Valizadeh, Hadi; Ketzis, Jennifer
Abstract: Background: Fish is a great nutritious food and provides quality protein and a variety of vitamins and minerals. This contributes significantly to the economy and food security in Iran. However, there are safety concerns related to the presence of zoonotic parasites. Objectives: The objective of this study is, therefore, to review fish‐borne zoonotic parasites in Iran. Methods: Keywords such as fish‐borne, parasites, zoonotic, Iran, and some names of fish‐borne zoonotic parasites were searched in databases including PubMed, Science Direct, Elsevier, SID, Magiran, Irandoc, Google Scholar and the World Health Organization. Results: The most common fish‐borne parasites with zoonotic potential identified in reports in the literature were the protozoa Balantidium spp., Myxobolus spp. and Sarcosystis sp.; the trematodes Heterophyes heterophyes and Clinostomum complanatum ; the cestodes Ligula intestinalis and Diphyllobothrium latum ; the nematodes Pseudoterranova sp., Anisakis spp., Contracaecum spp., Raphidascar is spp., Eustrongylides spp. and Capillaria sp.; and the acanthocephal Corynosoma spp. Conclusions: The potential risk factors for the transmission of fish‐borne zoonotic parasites to humans are consumption of raw or undercooked infected fish, contact with contaminated water and contact with infected fish. There is a need for epidemiological surveillance of fish for parasites with zoonotic potential and of occurrence of infections in humans to better understand the public health significance and design prevention programs. Abstract :